EFEKTIVITAS MANAJEMEN PONDOK PESANTREN JAM’IYYAH ISLAMIYYAH TANGERANG SELATAN: PENDEKATAN BALANCED SCORECARD - Athoillah Islamy; Saihu Saihu (Balai Penelitian dan Pengembangan Agama Jakarta, 2021)
This paper aims to determine the effectiveness of the management in Islamic boarding schools using balanced scorecard performance analysis, including four perspectives: finance, customers, internal business processes and learning and growth in Jam'iyyah Islamiyyah Islamic Boarding School. This research uses a qualitative approach with a descriptive model. Based on the research that has been done, it is known that the management of Jam'iyyah Islamiyyah Islamic Boarding School measured with balanced scorecard approach is categorized as good, as the measurement results in all four perspectives are close to the expected target. After being measured using balanced scorecard approach and then analyzed with the effectiveness indicators according to Danim, the results show that the management of the Jam'iyyah Islamiyyah Islamic Boarding School can be said to be effective.